Pannotia: In defence of its existence and geodynamic significance - Murphy, J. Brendan; Nance, R.D.; Cawood, P.A.; Collins, William; Dan, W.; Doucet, Luc; Heron, P.J.; Li, Zheng-Xiang; Mitchell, R.N.; Pisarevsky, Sergei; Pufahl, P.K.; Quesada, C.; et al. (2021)
The status of Pannotia as an Ediacaran supercontinent, or even its mere existence as a coherent large landmass, is controversial. The effect of its hypothesized amalgamation is generally ignored in mantle convection models claiming the transition from Rodinia to Pangaea represents a single supercontinent cycle. We apply three geodynamic scenarios to Pannotia amalgamation that are tested using regional geology. Scenarios involving quasi-stationary mantle convection patterns are not supported by the geological record. A scenario involving feedback between the supercontinent cycle and global mantle convection patterns predicts upwellings beneath the Gondwanan portion of Pannotia and the arrival of plumes along the entire Gondwanan (but not Laurentian) margin beginning at c. 0.6 Ga. Such a scenario is compatible with regional geology, but the candidates for plume magmatism we propose require testing by detailed geochemical and isotopic studies. If verified, this scenario could provide geodynamic explanations for the origins of the late Neoproterozoic and Early Paleozoic Iapetus and Rheic oceans and the terranes that were repeatedly detached from their margins.